Fishing activities shape the flight behaviour of an opportunistic predator species. (5th November 2022) - Ouled-Cheikh, Jazel; Ramírez, Francisco; Sánchez-Fortún, Moisès; Cortejana, Augusto; Sanpera, Carola; Carrasco, Josep Lluís
Abstract: Human activities provide opportunistic species with abundant and predictable feeding opportunities that may shape their ecology, including their movement patterns and behaviour. Investigating human-wildlife interactions in marine ecosystems is challenging because of the logistic constraints of surveying vast and remote geographical areas. Fortunately, miniaturized biologging devices now provide the possibility of assessing the influence of human activities on marine life, particularly in the case of large-sized predators. Here, we used GPS tracking data for Mediterranean endemic Audouin's gulls, Ichthyaetus audouinii, to quantitatively characterise gulls' foraging trips and evaluate individuals' foraging behaviour in relation with fisheries. By using ca. 38, 090 space-time locations (i.e., 362 foraging trips), we calculated eight flight behaviour movement metrics to describe gull's flight behaviour within foraging trips. We used these movement metrics to analyse individuals' flight behaviour in contrasting fishing activity scenarios (i.e., presence/absence of fishing activity by trawlers and purse-seiners) and in response to spatial-temporal co-occurrence with fishing vessels operating in the area. Our results showed that Audouin's gulls adapted their flight behaviour in response to fisheries. When fishing vessels were active (particularly trawlers), gulls flew faster (particularly when co-ocurring with a fishing vessel) and more directly (i.e. lower directional changes), compared to non-fishing situations or when temporally co-occurring with purse seiners. This work enhances our understanding on seabird-fishery interactions, and may contribute to further evaluations on species responses to resource shortage scenarios, such as the collapse of local fish stocks and landing obligations. Beyond this ecological information, our results may also contribute to the use of seabirds for monitoring fisheries, and help fight Illegal, Unreported and Unregulated fishing (IUU) in areas where fishing vessels cannot be monitored by other means (e.g., through Vessel Monitoring Systems -VMS- or Automatic Monitoring Systems -AIS-). Highlights: Human activities provide opportunistic species with predictable feeding opportunities that may shape their behaviour. We used GPS tracking data for Audouin's gulls to evaluate their foraging behaviour in relation with human fisheries. Gulls flew faster and more directly when interacting with trawlers than with purse seiners or in no fishing situations. Our results provide new information about the behaviour of a Mediterranean endemic species.